The Role of (Line‐Field Confocal) Optical Coherence Tomography and Reflectance Confocal Microscopy in the Diagnosis of a Malignant Eccrine Differentiated Sweat Gland Tumour With Features of a Porocarcinoma and an Eccrine Spiradenocarcinoma: A Case Report - Schuh, Sandra; Mozaffari, Marco; Fünfer, Kristina; Heinz, Wera; Mayer, Oliver Jonas; Schlingmann, Sophia; Mireles Canales, Martha Paola; Winkler, Deborah; Thölken, Karisa; Bachter, Uta; Welzel, Julia (JEADV clinical practice, 2025)
ABSTRACT Malignant eccrine differentiated sweat gland tumours, including porocarcinoma and eccrine spiradenocarcinoma, are rare and aggressive neoplasms that pose diagnostic and therapeutic challenges. This case report aims to describe the role of in‐vivo and ex‐vivo line‐field confocal optical coherence tomography (LC‐OCT), optical coherence tomography (OCT), and ex‐vivo fusion confocal microscopy (evFCM) in diagnosing and assessing the margins of a malignant eccrine differentiated sweat gland tumour with features of both porocarcinoma and eccrine spiradenocarcinoma. An 84‐year‐old man presented with a nodular scalp lesion. The lesion was evaluated using dermoscopy, OCT, in‐vivo and ex‐vivo LC‐OCT and evFCM. The findings were followed by Mohs micrographic surgery and histopathological examination to confirm the diagnosis. Dermoscopy revealed a vascular pattern with polymorphous vessels, while in vivo LC‐OCT and OCT demonstrated large nodules with necrotic areas and cuboidal cells. Ex‐vivo LC‐OCT and evFCM confirmed the complete tumour excision, corroborated by histology. Histopathologic evaluation identified a malignant epithelial tumour with two components: epithelioid clusters mimicking glandular lumina and polymorphic cells with pronounced pleomorphism. The diagnosis of a malignant eccrine differentiated sweat gland tumour with features of porocarcinoma and eccrine spiradenocarcinoma was made. This case highlights the utility of LC‐OCT, OCT, and evFCM in diagnosing and managing malignant eccrine differentiated sweat gland tumours. These noninvasive imaging techniques offer near‐histological resolution, enabling more precise diagnosis and margin assessment. Further studies are warranted to validate these findings and improve diagnostic protocols for such rare tumours. Capsule summary This case report highlights the diagnostic value of line‐field confocal optical coherence tomography (LC‐OCT), optical coherence tomography (OCT), and ex‐vivo fusion confocal microscopy (evFCM) in identifying and managing a rare malignant eccrine sweat gland tumor with features of porocarcinoma and eccrine spiradenocarcinoma. These imaging techniques provided near‐histological resolution, aiding in accurate diagnosis and margin assessment, which was confirmed through histopathology and Mohs surgery.